Collaborative barriers among University - Industry - Policy (U-I-P) entities on environmental matters: a case study in Sarawak, Malaysia - Manyie, Janice; Gerusu, Geoffery James; Kueh, Roland Jui Heng (Technium Science, 2020)
Realizing the importance of practicing environmental concern, it is needed to understand the tools used to tackle the issues. In this study, university - industry - policy (U-I-P) entities collaboration is a significant approach that was viewed to be the success factor towards the efforts of tackling environmental issues. Collaboration work, which involves different entities benefit in a way that pushes the entities to move towards shared objectives and goals which is to improve the environmental condition. However, although the significance of U-I-P entities collaboration was known and the linkages among U-I-P entities has started, there are still limited information on the practice of collaboration specifically on the U-I-P entities linkage structures on environmental matters in Sarawak. Thus, there is a need to identify the barriers and success factor in order to develop successful collaboration. This study addressed the gap through a mixed method of qualitative and quantitative approaches which the data were collected from 199 respondents based on a face to face interview using structured questionnaires in the major divisions of Sarawak. Drawing from a large scale of study, the study explores the status of collaboration and the barriers of collaboration in Sarawak. Findings indicated that cost, private knowledge and knowledge barrier to be a major hurdle that inhibit the development of collaboration. The assessment suggested that more efforts to increase awareness on collaboration be disseminated.